Extubação paliativa: experiência de quatro casos em unidade de terapia intensiva neonatal - Inês Barros Rua; Marta Vidal; Joana Calvão; Rui Castelo; Leonor Ramos (Sociedade Brasileira de Pediatria, 2023)
Newborns may develop blisters and erosions due to multiple entities, including infections, congenital or hereditary diseases. In this report we describe a male newborn who presented with pustular lesions on the first day of life and progressively developed blisters and erosions. Due to disease progression even with intravenous antibiotic therapy after suspicion of bullous impetigo, other diagnoses had to be considered and a multidisciplinary approach with the support of dermatology was necessary. A skin biopsy and genetic study were performed, which allowed the definitive diagnosis of Epidermolysis Bullosa, a group of rare hereditary bullous diseases. Because of the absence of curative therapy, supportive treatment was performed, which did not prevent the patients death at 2 months of life. It is therefore essential for pediatricians to identify this entity as early as possible in order to improve the prognosis.